Hydrogel Microneedle for Controlled Delivery - Ashwini Ashok Kathale,; Neha N. Kadam, (Asian Journal of Pharmaceutical Research and Development, 2025)
Transdermal drug delivery (TDD) using hydrogel-forming microneedles (HFMs) is the subject of this review paper. HFMs, in contrast to traditional microneedles, are composed of cross-linked hydrophilic polymers that expand when applied topically to create microchannels for regulated and prolonged drug delivery. Their unique properties, including mechanical strength, antibacterial activity, biocompatibility, and biodegradability, make them very adaptable for both therapeutic and diagnostic applications. The paper describes the classes of microneedles (hydrogelforming, swellable, solid, coated, hollow, and dissolving), the natural and synthetic polymers employed in their manufacture (e.g., chitosan, gelatin, hyaluronic acid, PVA, PEG, PVP), and manufacture technique's like micro-molding and 3D printing. It also points towards their mechanisms in controlled release systems, uses in chronic disease treatment, infectious disease therapy, wound healing, and drug delivery, and assessment methods. HFMs have various benefits over traditional microneedles, such as improved drug loading capacity, safe removal without residue, non-invasive fluid extraction, and single-step application.